Proses Collaborative Governance dalam Penanganan Bullying di UPT SD Negeri 206 Gresik - Viona Erlanda; Anggraeny Puspaningtyas (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2023)
Bullying is a negative behavior carried out by a group of people to individuals who intend to harm physically, verbally, socially, or cyber until the victim is depressed. Bullying is now rampant among schools, therefore research was conducted at SD Negeri 206 Gresik on handling bullying using the theory of collaborative governance in the collaboration process according to Ansell and Gash. This study aims to determine how the role of stakeholders involved in handling bullying prevention. The research method used is descriptive method with a qualitative approach and data collection techniques using primary data by conducting documentation, observation, and interviews and secondary data with references from journals. The handling of bullying prevention at UPT SD Negeri 206 Gresik is optimal as evidenced by the absence of very severe bullying problems. In dealing with this, there needs to be a good collaboration between related stakeholders in order to achieve the expected goals. From the temporary results seen, it is expected from the school not to underestimate the problem of bullying even though what the student does is not severe.